Pre-culture of mesenchymal stem cells within RGD-modified hyaluronic acid hydrogel improves their resilience to ischaemic conditions - Gallagher, Laura B; Dolan, Eimear B; O'Sullivan, Janice; Levey, Ruth; Cavanagh, Brenton L; Kovarova, Lenka; Pravda, Martin; Velebny, Vladimir; Farrell, Tom; O'Brien, Fergal J; Duffy, Garry P (Acta biomaterialia, 2020)
The incorporation of the RGD peptide (arginine-glycine-aspartate) into biomaterials has been proposed to promote cell adhesion to the matrix, which can influence and control cell behaviour and function. While many studies have utilised RGD modified biomaterials for cell delivery, few have examined its effect under the condition of reduced oxygen and nutrients, as found at ischaemic injury sites. Here, we systematically examine the effect of RGD on hMSCs in hyaluronic acid (HA) hydrogel under standard and ischaemic culture conditions, to elucidate under what conditions RGD has beneficial effects over unmodified HA and its effectiveness in improving cell viability. Results demonstrate that under standard culture conditions, RGD significantly increased hMSC spreading and the release of vascular endothelial factor-1 (VEGF) and monocyte chemoattractant factor-1 (MCP-1), compared to unmodified HA hydrogel. As adhesion is known to influence cell survival, we hypothesised that cells in RGD hydrogels would exhibit increased cell viability under ischaemic culture conditions. However, results demonstrate that cell viability and protein release was comparable in both RGD modified and unmodified HA hydrogels. Confocal imaging revealed cellular morphology indicative of weak cell adhesion. Subsequent investigations found that RGD was could exert positive effects on encapsulated cells under ischaemic conditions but only if hMSCs were pre-cultured under standard conditions to allow strong adhesion to RGD before exposure. Together, these results provide novel insight into the value of RGD introduction and suggest that the adhesion of hMSCs to RGD prior to delivery could improve survival and function at ischaemic injury sites. STATEMENT OF SIGNIFICANCE: The development of a biomaterial scaffold capable of maintaining cell viability while promoting cell function is a major research goal in the field of cardiac tissue engineering. This study confirms the suitability of a modified HA hydrogel whereby stem cells in the modified hydrogel showed significantly greater cell spreading and protein secretion compared to cells in the unmodified HA hydrogel. A pre-culture period allowing strong adhesion of the cells to the modified hydrogel was shown to improve cell survival under conditions that mimic the myocardium post-MI. This finding may have a significant impact on the use and timelines of modifications to improve stem cell survival in harsh environments like the injured heart.
Keywords: Cell Survival; Tissue Engineering; Humans; tkáňové inženýrství; Oligopeptides; hydrogely; hypoxie buňky; viabilita buněk; Tissue Scaffolds; Cell Adhesion; lidé; oligopeptidy; tkáňové podpůrné struktury; mezenchymální kmenové buňky; kyselina hyaluronová; Hydrogels; buněčná adheze; Cell Culture Techniques; Hyaluronic Acid; Cell Hypoxia; Mesenchymal Stem Cells; buněčné kultury